Well Installation Procedures for Agricultural Irrigation in Miami-Dade County - Kati W. Migliaccio; E. Vanessa Campoverde; Ann Marie Superchi (EDIS)
Water wells or groundwater wells are the main source of irrigation water for agriculture in Miami-Dade County. Depending on the purpose and characteristics of the well, different permits are required for installing the well and pumping water from the well. The information provided in this 4-page fact sheet is based on current rules, contacts, and prices as of March 2012 for Miami-Dade County. Written by Kati W. Migliaccio, E. Vanessa Campoverde, and Ann Marie Superchi, and published by the UF Department of Agricultural and Biological Engineering, June 2012.